Kepemimpinan transformasional, budaya dan komitmen organisasi di kementerian kesehatan - Esrika Lamashinta; Noor Siti Rahmani; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2016)
Transformational leadership, organizational culture and commitment in the Ministry of HealthPurposeThis study aimed to analyze the relationship of organizational culture on organizational commitment and transformational leadership that would affect performance. MethodsThis study was conducted using a survey including 137 civil servants, from four units which were finance; programs and information; law, organization and public relations; and public and staffing. ResultsThere was a correlation between the variables of transformational leadership and organizational culture and organizational commitment of 26%. Organizational culture variables had the a stronger influence on changes in the value of organizational commitment than transformational leadership. Interviews showed leadership and organizational culture had been influential and running but not all went well mostly because of routine.ConclusionTransformational leadership and organizational culture were inseparable and mutually supportive in influencing the level of commitment of the organization's employees within the organization.